Aerogel composite material with temperature sensing function and preparation method thereof
Patent Information
- Application Number
- CN202611108147.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-11-03
AI Technical Summary
Traditional contact temperature sensors are difficult to install in nuclear power plants, their signals are easily interfered with, and their performance is easily degraded under strong radiation environments. They are difficult to monitor the status of insulation layers in real time and intuitively, posing safety hazards.
Using aerogel composite material with temperature sensing function, the radiation-resistant nanoporous aerogel is enhanced by inorganic unit modification of ultrafine fiber skeleton. The material itself has reversible color change to indicate temperature and damage status, without the need for external power supply and complicated circuitry.
It enables the visualization and perception of the actual temperature and thermal insulation effect of insulation materials within the temperature range of 300~600°C, provides early warning of damage, adapts to the multi-physical field coupling environment of nuclear power plants such as high temperature, vibration and strong radiation, and ensures mechanical strength and thermal structural stability.
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal insulation materials technology, and in particular to an aerogel composite material with temperature sensing function and its preparation method. Background Technology
[0002] High-temperature fast reactors, with their high power density and low-pressure, high-temperature characteristics, have become an important development direction for advanced nuclear energy systems. Their heat transfer directly affects the reactor's thermal efficiency and safety, primarily relying on high-temperature liquid metal (such as sodium, lead-bismuth alloys, etc.) coolants through the primary loop system. The integrity of the insulation layers of the pipes and equipment carrying these high-temperature liquid metal flows is of paramount importance for maintaining system thermal balance, ensuring safe operation, and improving power generation efficiency.
[0003] Aerogel materials, due to their extremely low thermal conductivity, have become ideal candidates for thermal insulation. Furthermore, reinforcement with microfibers can significantly improve their mechanical properties and structural stability, resulting in composite materials that combine excellent mechanical and thermal insulation performance. However, nuclear power plants have extremely compact piping and equipment layouts and limited space, while also facing harsh environments such as high noise, high temperatures, and strong radiation. These complex conditions make it difficult to install traditional contact temperature sensors, as their signals are susceptible to interference and pose risks such as radiation damage, hindering real-time and intuitive monitoring of the insulation layer's condition. If the insulation layer fails due to aging, vibration, or accidental impact, or if a minor leak occurs in the internal high-temperature metal pipes, failure to detect it promptly could trigger a chain reaction of localized overheating or corrosive media erosion, leading to serious safety accidents. Summary of the Invention
[0004] In view of this, to address the technical problems of existing nuclear power insulation materials being unable to directly indicate service temperature in situ, making it difficult to provide timely warnings of insulation failure and structural damage, and the easy degradation of the performance of conventional aerogels under the strong radiation environment of nuclear power plants, this invention provides an aerogel composite material with temperature sensing function and its preparation method. It integrates temperature sensing, high-efficiency heat insulation and radiation resistance, and can adapt to the multi-physics field environment of nuclear power plants. It does not require an external power supply or complex wiring. It can directly, in situ and in real time indicate the true surface temperature, heat insulation effect and damage status of the insulation layer through the material's own reversible color change. Thus, it provides an innovative solution with important engineering significance and safety value for realizing online monitoring of the health status and early warning of faults of key parts of advanced nuclear energy systems such as high-temperature fast reactors.
[0005] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides an aerogel composite material with temperature sensing function, which is composed of an inorganic unit modified ultrafine fiber skeleton reinforced with temperature sensing function and radiation-resistant nanoporous aerogel. The inorganic unit is uniformly coated on the ultrafine fiber skeleton in the form of a coating, uniformly dispersed between the ultrafine fiber skeleton in the form of powder, and / or uniformly dispersed inside the ultrafine fiber skeleton in the form of powder. The volume fraction of the inorganic unit is 15% to 25%, and the volume fraction of the ultrafine fiber skeleton is 20% to 35%. The inorganic unit is Al 3+ Doping with VO2, Ga 3+ Doping with VO2 and Cr 3+ Doping with VO2 and Ti 3+ Doping with VO2 or Cr 3+ Doping with Al2O3, in which Al 3+ Doping concentration of 1.0~5.0 mol% Ga 3+ The doping concentration is 0.5~3.0 mol%, Cr 3+ The doping concentration is 0.8~4.0 mol% Ti 3+ The doping concentration is 0.5~6.0 mol%, Cr 3+ Cr in Al2O3 3+ The doping concentration is 1~8.0 mol% The ultrafine fibers in the ultrafine fiber skeleton are one or more of the following: glass fiber, carbon fiber pre-oxidized cotton, mullite fiber, quartz fiber, alumina fiber, zirconium oxide fiber, and silicon carbide fiber. The radiation-resistant nanoporous aerogel is Gd 3+ Eu 3+ 、Sm 3+ Er 3+ Dy 3+ B 3+ One or more ion-doped SiO2 aerogels.
[0006] Secondly, the present invention provides the application of the above-mentioned aerogel composite material with temperature sensing function in nuclear power plants. When used in nuclear power plants, the aerogel composite material with temperature sensing function is wrapped around the outer layer of the insulation material. The color change of the aerogel composite material with temperature sensing function is used to detect its true temperature and true insulation effect in the service environment, indicating and warning of the occurrence of damage. The temperature sensing range of the aerogel composite material with temperature sensing function is 300~600°C.
[0007] Thirdly, the present invention provides a method for preparing the above-mentioned aerogel composite material with temperature sensing function, wherein when the inorganic unit uniformly coats the ultrafine fiber skeleton in the form of a coating, the method includes the following steps: (3.1) Ultrafine fibers are prepared by flame blowing or centrifugal blowing; (3.2) Ultrafine fibers with temperature sensing function are prepared by compositing inorganic units with temperature sensing function on the surface of ultrafine fibers using a hydrothermal synthesis method. The coating thickness of the inorganic unit is 0.1~500 μm. (3.3) Use a water-based self-assembly method to prepare ultra-thin felt from ultrafine fibers with temperature sensing function; (3.4) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in an ultrathin felt to obtain an ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power. When inorganic units are uniformly dispersed in powder form between ultrafine fiber skeletons, the following steps are included: (4.1) Ultrafine fibers are prepared by flame blowing or centrifugal blowing methods; (4.2) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; (4.3) Microspheres of inorganic unit powder coated with SiO2 with temperature sensing function were prepared by the interface confined sol-gel method. The microspheres have a core-shell structure with a shell thickness of 20~1000 nm. (4.4) Using ultrafine fibers and SiO2-coated inorganic unit microspheres with temperature sensing function as raw materials, a water-based self-assembly method was used to prepare fiber felt loaded with inorganic unit powder with temperature sensing function; (4.5) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in the fiber felt to obtain ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power. When inorganic units are uniformly dispersed in powder form within ultrafine fibers, the following steps are included: (5.1) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; (5.2) Ultrafine fibers with embedded inorganic unit powders having temperature sensing function are prepared by electrospinning or centrifugal spinning. (5.3) Nanofiber-derived aerogels with layered multi-level pores were prepared by water-based self-assembly or freeze-drying methods; (5.4) Radiation-resistant nanoporous aerogels were in situ composited in nanofiber-derived aerogels using a sol-gel combined supercritical drying method.
[0008] Compared with the prior art, the present invention has the following beneficial effects: (1) The ultrafine glass fiber reinforced aerogel composite material of the present invention has a temperature sensing function, which can realize the visualization of the real temperature and heat insulation effect of the insulation material in the temperature range of 300~600°C, and intuitively reflect the real temperature and heat insulation status of the covered insulation material, thereby providing early warning of damage and realizing early, intuitive and in-situ observation of damage or failure. (2) The ultrafine fiber-reinforced radiation-resistant aerogel structure endows the composite material with excellent thermal insulation, noise reduction and radiation resistance properties, ensuring good mechanical strength and thermal structural stability, and enabling it to adapt to the extreme service environment of nuclear power plants with high temperature, vibration and strong radiation and other multi-physical field coupling. It has important application value in the field of nuclear power insulation materials.
[0009] (3) The leakage of molten metal in nuclear power pipelines leads to a local temperature rise. The location of the damage can be detected in time by using aerogel composite materials with temperature sensing function to avoid nuclear power accidents. (4) The composite material structure of the present invention is flexible and can be adapted to different needs by adjusting the composite method and type of inorganic units. Its technical principle and preparation method are not only applicable to high temperature fast reactors, but also provide innovative solutions for other industrial fields that require high temperature insulation and condition monitoring. Detailed Implementation
[0010] This invention provides an aerogel composite material with temperature sensing function, which is composed of an inorganic unit modified ultrafine fiber skeleton reinforced with temperature sensing function and radiation-resistant nanoporous aerogel. The inorganic unit is uniformly coated on the ultrafine fiber skeleton in the form of a coating, uniformly dispersed between the ultrafine fiber skeleton in the form of powder, and / or uniformly dispersed inside the ultrafine fiber skeleton in the form of powder. The volume fraction of the inorganic unit is 15% to 25%, and the volume fraction of the ultrafine fiber skeleton is 20% to 35%.
[0011] In one specific embodiment of the present invention, the inorganic unit is Al. 3+ Doping with VO2, Ga 3+ Doping with VO2 and Cr 3+ Doping with VO2 and Ti 3+ Doping with VO2 or Cr 3+ Doping with Al2O3, in which Al 3+ Doping concentration of 1.0~5.0 mol% Ga 3+ The doping concentration is 0.5~3.0 mol%, Cr 3+ The doping concentration is 0.8~4.0 mol% Ti 3+ The doping concentration is 0.5~6.0 mol%, Cr 3+ Cr in Al2O33+ The doping concentration is 1~8.0 mol%.
[0012] In one specific embodiment of the present invention, the ultrafine fibers in the ultrafine fiber skeleton are one or more of the following fibers: glass fiber, carbon fiber pre-oxidized cotton, mullite fiber, quartz fiber, alumina fiber, zirconium oxide fiber, and silicon carbide fiber.
[0013] In one specific embodiment of the present invention, the radiation-resistant nanoporous aerogel is Gd 3+ Eu 3+ 、Sm 3+ Er 3+ Dy 3+ B 3+ One or more ion-doped SiO2 aerogels.
[0014] This invention provides the application of the above-mentioned temperature-sensing aerogel composite material in nuclear power plants. When used in nuclear power plants, the temperature-sensing aerogel composite material is coated on the outer layer of the insulation material. The color change of the temperature-sensing aerogel composite material is used to detect its true temperature and true insulation effect in the service environment, indicating and warning of damage. The temperature sensing range of the temperature-sensing aerogel composite material is 300~600°C.
[0015] This invention also provides a method for preparing the above-mentioned aerogel composite material with temperature sensing function, which includes the following steps when inorganic units uniformly coat the ultrafine fiber skeleton in the form of a coating: Step (3.1) involves preparing ultrafine fibers using either flame blowing or centrifugal blowing methods; Step (3.2) uses a hydrothermal synthesis method to composite inorganic units with temperature sensing function on the surface of ultrafine fibers to prepare ultrafine fibers with temperature sensing function. The thickness of the inorganic unit coating is 0.1~500 μm. Step (3.3) uses a water-based self-assembly method to prepare ultra-thin felt from ultrafine fibers with temperature sensing function; Step (3.4) uses a sol-gel combined supercritical drying method to in-situ composite radiation-resistant nanoporous aerogel in an ultrathin felt to obtain an ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power. When inorganic units are uniformly dispersed in powder form between ultrafine fiber skeletons, the following steps are included: (4.1) Ultrafine fibers are prepared by flame blowing or centrifugal blowing methods; (4.2) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; (4.3) Microspheres of inorganic unit powder coated with SiO2 with temperature sensing function were prepared by the interface confined sol-gel method. The microspheres have a core-shell structure with a shell thickness of 20~1000 nm. (4.4) Using ultrafine fibers and SiO2-coated inorganic unit microspheres with temperature sensing function as raw materials, a water-based self-assembly method was used to prepare fiber felt loaded with inorganic unit powder with temperature sensing function; (4.5) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in the fiber felt to obtain ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power. When inorganic units are uniformly dispersed in powder form within ultrafine fibers, the following steps are included: (5.1) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; (5.2) Ultrafine fibers with embedded inorganic unit powders having temperature sensing function are prepared by electrospinning or centrifugal spinning. (5.3) Nanofiber-derived aerogels with layered multi-level pores were prepared by water-based self-assembly or freeze-drying methods; (5.4) Radiation-resistant nanoporous aerogels were in situ composited in nanofiber-derived aerogels using a sol-gel combined supercritical drying method.
[0016] In one specific embodiment of the present invention, step (3.2) of the hydrothermal synthesis method includes the following steps: When the inorganic unit is doped with VO2: ① A vanadium source, reducing agent, and doped metal salt are dissolved in deionized water at a molar ratio of 1:(0.8~3.0):(0.015~0.10) to prepare a 0.1~0.5 mol / L solution, so that the doped ions enter the VO2 lattice to replace the vanadium sites and adjust the phase transition temperature. The vanadium source is ammonium metavanadate or vanadium pentoxide, the reducing agent is oxalic acid or hydrazine hydrate, and the doped metal salt is aluminum nitrate, gallium nitrate, chromium nitrate, or tetrabutyl titanate. ② Adjust the pH to 2.0~3.5 with hydrochloric acid or nitric acid to prevent precipitation and facilitate the formation of pure VO2 phase; ③ Place the mixed solution and ultrafine fibers together in a reaction vessel at a mass ratio of (10~30):1, and keep it at 160~240℃ for 8~32 h to promote hydrothermal crystallization and heterogeneous nucleation on the fiber surface, making the coating more dense; ④ After cooling, wash with deionized water until neutral, and dry at 50~100℃ for 4~16 h; ⑤ Calcination at 350~550℃ for 0.5~4 h under an inert atmosphere further crystallizes and removes residual hydroxyl groups, stabilizing the VO2 phase structure to obtain ultrafine fibers with surface-coated doped and modified VO2. When the inorganic unit is Cr 3+ When doped with Al2O3: ① Dissolve an aluminum source and a chromium source in deionized water at a molar ratio of 1:(0.01~0.08) to prepare a solution of 0.2~0.6 mol / L. The aluminum source is aluminum isopropoxide or aluminum nitrate, and the chromium source is chromium nitrate, chromium trichloride or chromium acetate. ② Adding α-Al2O3 or magnesium oxide as a phase transformation inhibitor can prevent cracks caused by the γ→α phase transformation at high temperatures and maintain the integrity of the coating. The amount added is 3% to 15% of the mass of the aluminum source. ③Immerse the microfiber in the above solution and vacuum impregnate for 20~90 min to remove air bubbles between the fibers and ensure that the solution fully wets the fibers. The vacuum degree is 0.05~0.095 MPa. ④ Dry at 60~150℃ for 2~12 h, then calcine at 900~1300℃ in air for 1~6 h to obtain Cr-coated surface. 3+ Ultrafine fibers doped with modified Al2O3.
[0017] In one specific embodiment of the present invention, steps (3.3), (4.4), and (5.3) of the water-based self-assembly method include the following steps: ① Using deionized water as a solvent, add ultrafine fibers with temperature sensing function to the solvent and sonicate for 5-60 min to uniformly disperse the fibers, thus preparing an ultrafine fiber dispersion; ② Add 0.1-5.0 wt% acrylate or polyvinyl alcohol as a binder to the above dispersion to provide bridging force at the fiber intersections, and mechanically stir to mix it evenly, thus obtaining an ultrafine fiber slurry; ③ When preparing the ultrathin felt body described in step (3.3), control the solid content of the slurry to be 1-25 wt%, stir at 300-5000 rpm for 10-120 min, then extract the evenly dispersed slurry to the molding system, and use vacuum filtration to assist molding, controlling the vacuum degree to be 0.01-0.15 MPa, so that the fibers are deposited on the molding mesh belt to form a wet felt, and then dry at 40-150℃ for 1-12 h to obtain a thickness of 0.1-5.0 mm. ④ When preparing the ultrathin felt body described in step (4.4), SiO2-coated inorganic unit microspheres are added simultaneously in step ①, and the solid content of the slurry is controlled to be 1~25 wt%. The slurry is stirred at 300~5000 rpm for 10~120 min, and then the uniformly dispersed slurry is extracted and transferred to the molding system. Vacuum filtration is used to assist molding, and the vacuum degree is controlled to be 0.01~0.15 MPa, so that the fibers are deposited on the molding mesh belt to form a wet felt. Then, it is dried at 40~150℃ for 1~12 h to obtain an ultrathin felt body with a thickness of 0.1~5.0 mm; ⑤ When preparing the nanofiber-derived aerogel described in step (5.3), the slurry is divided into two types: type A slurry and type B slurry. The solid content of type A slurry is 0.5~5.0 wt%, the binder content is 0.5~5.0 wt%, and the solid content of type B slurry is 0.1~2.0 wt%. The binder content is 0.1~2.0 wt%; the nanofiber-derived aerogel with a layered multi-level porous structure is obtained by layered filtration molding and gradient drying molding.
[0018] In one specific embodiment of the present invention, steps (3.4), (4.5), and (5.4) of the sol-gel combined supercritical drying method include the following steps: ① Prepare a silica sol by mixing tetraethyl orthosilicate, ethanol, and deionized water in a molar ratio of 1:(6~12):(4~10). Use hydrochloric acid or ammonia as a catalyst to hydrolyze and condense tetraethyl orthosilicate to form a three-dimensional network. The amount of catalyst used is 0.5%~3% of the total mass of the silica sol. Dissolve a dopant metal source in deionized water or ethanol. The dopant metal source is gadolinium nitrate, europium nitrate, samarium nitrate, erbium nitrate, dysprosium nitrate, or boric acid. Control the total molar concentration of dopant ions to be 0.01~0.20 mol / L. The volume ratio of the dopant metal source solution to the silica sol is 1:(5~20). Mix the dopant solution and silica sol evenly so that the dopant ions enter the framework through chemical bonds or physical doping. ② Immerse the ultrathin felt body described in steps (3.3) and (4.4) or the nanofiber-derived aerogel described in step (5.3) into the sol prepared in ① under a vacuum of 0.04~0.095. ③ Impregnate the sample at 30-80℃ for 20-90 min to remove air from the fiber bundles and ensure that the sol fully penetrates into the fiber network to achieve in-situ composite; ④ Place the impregnated sample in a sealed container and let it stand at 30-80℃ for 8-32 h to allow the sol to gel in-situ within the fiber skeleton; ⑤ Continue aging the gel composite system at 30-80℃ for 12-72 h to enhance the strength of the gel network; ⑥ Use anhydrous ethanol for solvent replacement, changing the solvent every 6-16 h for 2-7 days to remove unreacted substances and moisture; ⑥ Use ethanol or carbon dioxide as the drying medium for supercritical drying at a temperature of 240-320℃, a pressure of 7.5-20 MPa, and a drying time of 2-8 h to finally obtain a microfiber reinforced aerogel composite material with temperature sensing function for nuclear power.
[0019] In one specific embodiment of the present invention, steps (4.2) and (5.1) of the precursor impregnation-thermal diffusion method include the following steps: A vanadium source (ammonium metavanadate or vanadium pentoxide) or an aluminum source (aluminum isopropoxide or aluminum nitrate) is dispersed in deionized water to form a suspension of 0.1–0.8 mol / L. Polyvinyl alcohol (PVA) is added (PVA acts as a dispersant and pore-forming agent to ensure uniform mixing of the precursors, resulting in well-crystallized doped powder after calcination). The mixture is then ultrasonically treated, with PVA accounting for 1%–5% of the suspension mass. The ultrasonic treatment lasts 20–60 min. A doping metal source, such as aluminum nitrate, gallium nitrate, chromium nitrate, or tetrabutyl titanate, is then added. The molar ratio of the doping metal source to the vanadium or aluminum source is (0.005–0.08):1. The mixture is heated and stirred in a water bath at 60–90°C for 2–6 h at a stirring speed of 300–800 rpm. The mixed solution is aged at room temperature for 12–48 h, and then dried in a drying oven at 80–120°C for 12–24 h. h, to obtain precursor blocks; place the precursor blocks in a muffle furnace or tube furnace, heat to 400-800℃ at a heating rate of 2-5℃ / min, and calcine in air or nitrogen / argon inert atmosphere for 2-6 h; cool the calcined product to room temperature, grind it in a ball mill or mortar for 10-60 min at a grinding speed of 200-500 rpm, and sieve to obtain inorganic unit powder with temperature sensing function with a particle size of 0.5-50 μm.
[0020] In one specific embodiment of the present invention, step (4.3) of the interface-confined sol-gel method includes the following steps: ① Disperse the temperature-sensing inorganic unit powder described in step (4.2) in an ethanol / oxalic acid mixed solution, with a volume ratio of ethanol to oxalic acid of (20~50):1 and an inorganic unit powder concentration of 0.05~0.3 g / mL. Add hexadecyltrimethylammonium bromide (CTAB) for surface activation, so that oriented micelles are formed on the powder surface, inducing uniform growth of the silica shell. The amount of CTAB is 5%~20% of the inorganic unit powder mass. ② Add tetraethyl orthosilicate solution dropwise, with a tetraethyl orthosilicate to inorganic unit powder mass ratio of (0.5~3):1, and adjust the pH to 2.5~4.5 so that the tetraethyl orthosilicate polycondensation mainly occurs on the powder surface, avoiding self-nucleation and improving the coating efficiency. ③ Stir the mixed solution in a 30~60°C water bath for 2~8 h at a stirring speed of 300~600 rpm. After interfacial confined polycondensation, let the mixed solution stand at room temperature for 12~48 hours. h, the aged suspension was centrifuged at 3000~8000 rpm for 5~15 min, and the precipitate was collected; the precipitate was washed 3~5 times with deionized water and anhydrous ethanol alternately, and centrifuged after each washing; the washed precipitate was dried in a drying oven at 60~120℃ for 6~18 h to obtain SiO2-coated inorganic unit powder microspheres with temperature sensing function.
[0021] In one specific embodiment of the present invention, step (5.2) of the electrospinning method includes the following steps: ① A spinning solution of 8-25 wt% is prepared by dissolving polyvinylpyrrolidone or polyvinylidene fluoride as the spinning polymer in N,N-dimethylformamide or ethanol; ② Inorganic unit powder with temperature sensing function is added at a rate of 5%-40% of the polymer mass; ③ After ultrasonic dispersion for 20-90 min, 0.3-0.8 wt% of a crosslinking agent is added to improve the viscoelasticity of the spinning solution and prevent powder sedimentation. The crosslinking agent is glutaraldehyde or N,N-methylenebisacrylamide. The solution is mechanically stirred for 2-6 h to obtain a uniform spinning solution; ④ The spinning solution is injected into an electrospinning device with a voltage of 12-30 kV, a receiving distance of 10-25 cm, and a feed speed of 0.3-3 mL / h to obtain precursor fibers; ⑤ The precursor fibers are calcined at 350-650℃ for 2-6 h to remove organic components. The calcination atmosphere is air to obtain ultrafine fibers with embedded inorganic units.
[0022] In one specific embodiment of the present invention, step (5.2) of the centrifugal spinning method includes the following steps: ① Using polyacrylonitrile or polylactic acid as the spinning polymer, dissolve it in dimethyl sulfoxide or acetone to prepare a polymer solution with a mass concentration of 8%–30%; ② Mix inorganic unit powder with the polymer solution, with a powder content of 10–45 wt%, and ultrasonically disperse for 20–120 min to break up powder agglomeration and uniformly suspend it to obtain a stable spinning solution; ③ Add the spinning solution to a centrifugal spinning device, set the rotation speed to 2000–10000 rpm, the nozzle diameter to 0.1–0.8 mm, and collect the fibers at a receiving distance of 8–20 cm; ④ After fiber collection, pre-oxidize at 60–150℃ for 12–48 h to form a heat-resistant trapezoidal structure, prevent melting during carbonization, and maintain the fiber morphology. The pre-oxidation atmosphere is air; ⑤ Carbonize at 450–800℃ for 2–6 h under nitrogen or argon protection to obtain ultrafine fibers with embedded inorganic units that have temperature sensing function.
[0023] In one specific embodiment of the present invention, step (5.3) of the freeze-drying method includes the following steps: ① Disperse ultrafine fibers with embedded temperature-sensing inorganic unit powders in deionized water to prepare a suspension of 0.5~3 wt%, and ultrasonically disperse for 30~180 min; ② Pour the fiber suspension into a freezing mold and pre-freeze at -20~-100℃ for 6~36 h, which can cause ice crystals to grow in a direction along the temperature gradient, compress the fibers to form an oriented structure, and form a gel with controllable pore morphology; ③ Transfer the gel to a freeze dryer and freeze-dry it at a vacuum of 0.5~20 Pa and a temperature of -40~-60℃ for 36~96 h to obtain a nanofiber-derived aerogel with layered multi-level pores.
[0024] The technical solution of the present invention will be clearly and thoroughly described below with reference to specific embodiments.
[0025] Example 1 A temperature-sensing ultrafine alumina fiber reinforced B material for insulation of sodium flow pipes in sodium-cooled fast reactors. 3+ Doped SiO2 aerogel composite material. Contains Al with temperature sensing function. 3+ VO2-doped inorganic unit modified ultrafine alumina fiber skeleton reinforced with radiation resistance B 3+ The material is composed of doped SiO2 nanoporous aerogel, with the temperature-sensing inorganic unit uniformly coated onto an ultrafine fiber skeleton in the form of a coating. In nuclear power applications, the temperature-sensing ultrafine fiber-reinforced aerogel composite material is coated onto the outer layer of the insulation material. The color change of the composite material is used to detect its actual temperature and insulation performance under service conditions, thereby indicating and warning of potential damage. The volume fraction of the temperature-sensing inorganic unit is 25%, the volume fraction of the ultrafine fiber is 20%, and Al... 3+ Al doped with VO2 inorganic units 3+ The doping concentration was 2.0 mol%, and the thickness of the inorganic unit coating was 20 μm.
[0026] Inorganic units are uniformly coated onto the ultrafine fiber skeleton in the form of a coating. A method for preparing ultrafine fiber reinforced aerogel composite materials with temperature sensing function for nuclear power includes the following steps: (1) Ultrafine alumina fibers were prepared by flame blowing method; (2) Temperature-sensing inorganic units were composited on the surface of ultrafine fibers using a hydrothermal synthesis method to prepare ultrafine fibers with temperature sensing function. First, ammonium metavanadate, oxalic acid and aluminum nitrate were dissolved in deionized water at a molar ratio of 1:1.5:0.02 to prepare a 0.2 mol / L solution. The pH was adjusted to 2.0 with hydrochloric acid. The mixed solution and ultrafine alumina fibers were placed together in a reaction vessel at a mass ratio of 20:1 and kept at 180℃ for 12 h. After cooling, the solution was washed with deionized water until neutral and dried at 80℃ for 12 h. Then, it was calcined at 400℃ for 1 h under an inert atmosphere to obtain Al-coated surface. 3+ Ultrafine alumina fibers doped with modified VO2; (3) The ultra-thin felt is prepared by using a water-based self-assembly method to make ultra-fine fibers with temperature sensing function. First, the ultra-fine fibers are dispersed in deionized water and ultrasonically treated for 30 min. 1.0 wt% of polyvinyl alcohol is added and mechanically stirred to make it uniformly mixed to obtain ultra-fine fiber slurry. The solid content of the slurry is controlled to be 10 wt%, and it is stirred at 1000 rpm for 60 min. The uniformly dispersed slurry is extracted to the molding system and molded by vacuum filtration. The vacuum degree is controlled to be 0.05 MPa, so that the fibers are deposited on the molding mesh belt to form a wet felt. Then, it is dried at 80℃ for 6 h to obtain an ultra-thin felt with a thickness of 1.0 mm. (4) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in an ultrathin felt to obtain a microfiber-reinforced aerogel composite material with temperature sensing function for nuclear power. First, a silica sol was prepared by mixing tetraethyl orthosilicate, ethanol, and deionized water in a molar ratio of 1:8:6, with hydrochloric acid as a catalyst, and the amount of catalyst was 1% of the total mass of the silica sol. Gadolinium nitrate was dissolved in ethanol to control Gd 3+ The molar concentration was 0.05 mol / L, and the volume ratio of the doping solution to the silica sol was 1:10. The doping solution and silica sol were mixed evenly. The ultrathin felt was immersed in the sol and impregnated under a vacuum of 0.06 MPa for 45 min. The impregnated sample was placed in a sealed container and allowed to stand at 50℃ for 16 h to allow the sol to gel in situ within the fiber skeleton. The gel composite system was further aged at 50℃ for 36 h. Solvent replacement was performed with anhydrous ethanol every 8 h for 4 days. Supercritical drying was carried out using ethanol as the drying medium at a supercritical drying temperature of 260℃, a pressure of 10 MPa, and a drying time of 4 h, thus obtaining ultrafine alumina fiber reinforced B with temperature sensing function. 3+ Doped SiO2 aerogel composite material.
[0027] The ultrafine fiber reinforced aerogel composite material prepared in this embodiment has a room temperature thermal conductivity of 0.028 W / (m·K), an average sound insulation of 28 dB in the 500~2000 Hz range, and a specific surface area retention rate of 92.3% after cumulative dose irradiation with 1700 kGy gamma rays, with a thermal conductivity increase of <8%. Meanwhile, Al... 3+ The VO2-doped coating exhibits reversible thermochromic changes (yellow-brown → gray-black) at 350–410°C with a response time <2 s and a threshold fluctuation <5°C after 50 cycles. A method for preparing nano-silica fiber-reinforced alumina aerogel, disclosed in patent CN116023165A, has a room-temperature thermal conductivity of 0.0413–0.0476 W / (m·K) and a compressive strength of only 78.3–88.5 kPa. Furthermore, it does not incorporate any radiation resistance design and lacks long-term stability under nuclear power radiation conditions. This embodiment reduces the thermal conductivity by approximately 32%–40% and simultaneously achieves integrated radiation resistance and visualized temperature sensing, demonstrating significant advantages in environmental adaptability to sodium flow pipelines in nuclear power sodium-cooled fast reactors.
[0028] Example 2 A temperature-sensing ultrafine glass fiber reinforced Gd2O3 material for insulation of lead-cooled fast reactor pipelines 3+ Doped SiO2 aerogel composite material. Contains Cr with temperature sensing function. 3+ This product is composed of an Al2O3-doped inorganic unit-modified ultrafine glass fiber skeleton reinforced with radiation-resistant nanoporous aerogel. The inorganic units are uniformly dispersed in powder form between the ultrafine fiber skeleton. In nuclear power applications, the ultrafine fiber-reinforced aerogel composite material with temperature sensing capabilities is coated onto the outer layer of the insulation material. The color change of the composite material is used to detect its actual temperature and insulation effect under service conditions, thereby indicating and warning of potential damage. The volume fraction of the temperature-sensing inorganic units is 20%, the volume fraction of the ultrafine fibers is 30%, and the Cr content is [not specified]. 3+ Cr in Al2O3 3+ The doping concentration was 5.0 mol%, and the thickness of the SiO2-coated microsphere shell was 50 nm.
[0029] Inorganic units are uniformly dispersed in powder form between ultrafine fiber skeletons. A method for preparing ultrafine fiber reinforced aerogel composite materials with temperature sensing function for nuclear power includes the following steps: (1) Ultrafine glass fibers were prepared by centrifugal blowing method; (2) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; aluminum isopropoxide was dispersed in deionized water to prepare a 0.3 mol / L suspension, and chromium nitrate was added to control the Cr content. 3+The doping concentration was 5.0 mol%; polyvinyl alcohol was added and ultrasonically dispersed for 30 min, stirred in an 80℃ water bath for 4 h, and aged for 12 h; dried at 120℃ for 24 h; heated to 600℃ at a heating rate of 5°C / min and calcined in air for 4 h; the calcined product was cooled to room temperature, ground in a ball mill for 30 min at a grinding speed of 300 rpm, and sieved to obtain Cr with a particle size of 2~10 μm. 3+ Al2O3 doped powder; (3) Microspheres of inorganic unit powder coated with SiO2 and having temperature sensing function were prepared by the interface confined sol-gel method. The microspheres have a core-shell structure. First, Cr 3+ Al₂O₃ doped powder was dispersed in an ethanol / oxalic acid mixed solution with a volume ratio of 30:1 and an inorganic unit powder concentration of 0.15 g / mL. Surface activation was performed by adding hexadecyltrimethylammonium bromide (CTAB), with the CTAB amount being 10% of the inorganic unit powder mass. Tetraethyl orthosilicate solution was added dropwise at a mass ratio of 1.5:1 to the inorganic unit powder, and the pH was adjusted to 3.5. The mixed solution was stirred at 450 rpm for 4 h in a 45°C water bath. After interfacial confined condensation, the mixed solution was aged at room temperature for 24 h. The aged suspension was centrifuged at 5000 rpm for 10 min, and the precipitate was collected. The precipitate was washed four times alternately with deionized water and anhydrous ethanol, centrifuged after each wash, and dried in an 80°C drying oven for 12 h to obtain SiO₂-coated Cr. 3+ Al2O3-doped microspheres with a shell thickness of 50 nm; (4) Using ultrafine fibers and SiO2-coated inorganic unit microspheres with temperature sensing function as raw materials, fiber mats loaded with inorganic unit powders with temperature sensing function are prepared by water-based self-assembly; firstly, ultrafine glass fibers and SiO2-coated Cr 3+ Al2O3 microspheres were dispersed in deionized water and ultrasonically treated for 30 min. 1.0 wt% polyvinyl alcohol was added and mechanically stirred to mix evenly to obtain a mixed slurry. The solid content of the slurry was controlled at 15 wt%, and the mixture was stirred at 800 rpm for 90 min. The evenly dispersed slurry was then drawn into a molding system and molded by vacuum filtration. The vacuum degree was controlled at 0.08 MPa to allow the fibers and microspheres to be deposited on the molding mesh to form a wet felt. The wet felt was then dried at 100℃ for 8 h to obtain a fiber felt with a thickness of 2.0 mm. (5) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in the fiber felt to obtain ultrafine fiber reinforced aerogel composite materials with temperature sensing function for nuclear power. First, a silica sol was prepared by mixing tetraethyl orthosilicate, ethanol, and deionized water in a molar ratio of 1:10:8, with ammonia as a catalyst, and the amount of catalyst was 1.5% of the total mass of the silica sol. Gadolinium nitrate was dissolved in deionized water to control Gd 3+ The molar concentration was 0.08 mol / L, and the volume ratio of the doping solution to the silica sol was 1:12. The doping solution and silica sol were mixed evenly. The fiber felt was immersed in the sol and impregnated under a vacuum of 0.08 MPa for 60 min. The impregnated sample was placed in a sealed container and allowed to stand at 60℃ for 24 h to allow the sol to gel in situ within the fiber skeleton. The gel composite system was further aged at 60℃ for 48 h. Solvent replacement was performed with anhydrous ethanol every 12 h for 5 days. Supercritical drying was carried out using carbon dioxide as the drying medium at a supercritical drying temperature of 280℃, a pressure of 12 MPa, and a drying time of 6 h, thus obtaining ultrafine glass fiber reinforced Gd with temperature sensing function. 3+ Doped SiO2 aerogel composite material.
[0030] The ultrafine fiber reinforced aerogel composite material prepared in this embodiment has a room temperature thermal conductivity of 0.032 W / (m·K), an average sound insulation of 26 dB in the 500~2000 Hz range, and a specific surface area retention rate of 90.5% after 1700 kGy γ irradiation, with a thermal conductivity increase of <10%. Meanwhile, Cr... 3+ The doped Al2O3 powder exhibits a fluorescent temperature response at 420–490°C with a resolution of ±3°C, and SiO2 coating ensures long-term stability. A method for preparing glass fiber reinforced organic-bridged silica aerogel, disclosed in patent CN121517186A, has a room-temperature thermal conductivity of 0.05671 W / (m·K) and a maximum compressive strength of only 0.08 MPa. Furthermore, the introduction of an organic bridging agent (diphenylmethane bismaleimide) leads to a decrease in flame retardancy, and the organic segments are easily degraded under the high-temperature radiation environment of nuclear power plants, lacking radiation resistance and temperature sensing capabilities. This embodiment reduces the thermal conductivity by approximately 44% while simultaneously achieving integrated radiation resistance and visual temperature sensing, demonstrating significant advantages in environmental adaptability for lead-cooled fast reactor pipelines in nuclear power plants.
[0031] Example 3 An ultrafine carbon fiber pre-oxidized cotton reinforced with temperature sensing function for insulation of hot gas ducts in high-temperature gas-cooled reactors. 3+ SiO2-doped aerogel composite material. Contains temperature-sensing Ti. 3+VO2-doped inorganic units are uniformly dispersed in powder form within the ultrafine carbon fiber pre-oxidized cotton skeleton, and combined with radiation-resistant Eu... 3+ It is composed of doped SiO2 nanoporous aerogel. In nuclear power applications, this composite material is used as a coating on the outer layer of insulation materials. Real-time temperature and insulation performance are monitored based on material color changes, providing early warning of potential damage. The inorganic unit volume fraction is 18%, the ultrafine fiber skeleton volume fraction is 28%, and Ti... 3+ The doping concentration is 3.0 mol%.
[0032] Inorganic units are uniformly dispersed in powder form within an ultrafine fiber framework. A method for preparing ultrafine fiber reinforced aerogel composite materials with temperature sensing capabilities for nuclear power applications includes the following steps: (1) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; ammonium metavanadate (vanadium source) was dispersed in deionized water to prepare a 0.5 mol / L suspension, and tetrabutyl titanate (doped metal source) was added to control the Ti 3+ The molar ratio of Ti to V was 0.03:1. Polyvinyl alcohol (3% of the suspension mass) was added as a dispersant, and the mixture was ultrasonically treated for 40 min. The mixture was stirred at 500 rpm for 4 h in an 80℃ water bath, aged at room temperature for 24 h, and then dried at 100℃ for 18 h to obtain precursor lumps. The lumps were placed in a tube furnace and heated to 650℃ at a rate of 3℃ / min, then calcined under argon protection for 5 h. After cooling, the mixture was ground in a mortar for 20 min and passed through a 300-mesh sieve to obtain Ti with a particle size of 1–5 μm. 3+ Doped with VO2 powder.
[0033] (2) Ultrafine fibers with embedded temperature-sensing inorganic unit powders were prepared by electrospinning; polyacrylonitrile (PAN) was used as the spinning polymer and dissolved in N,N-dimethylformamide (DMF) to prepare a spinning solution with a mass concentration of 12%. The Ti obtained in step (1) was then used to prepare the spinning solution. 3+VO2-doped powder was added to the spinning solution at 30% of the polymer mass and ultrasonically dispersed for 60 min (200 W power) to ensure uniform suspension. Then, glutaraldehyde (0.5% of the spinning solution mass) was added as a crosslinking agent, and the solution was mechanically stirred for 4 h to obtain a uniform and stable spinning solution. The spinning solution was injected into an electrospinning apparatus using a 0.6 mm inner diameter stainless steel needle, with an applied voltage of 18 kV, a receiving distance of 15 cm, a feed rate of 1.0 mL / h, and the ambient temperature controlled at 25℃ with a relative humidity below 40%. Aluminum foil was used as the receiving plate to collect the nonwoven precursor fiber membrane. The collected precursor fiber membrane was placed in air and heated to 260℃ at a rate of 2℃ / min, and held for 2 h for pre-oxidation treatment to form a heat-resistant trapezoidal structure in the PAN fibers, thus obtaining ultrafine carbon fiber pre-oxidized cotton. The average fiber diameter was approximately 300–800 nm, with the powder uniformly embedded within the fibers.
[0034] (3) Nanofiber-derived aerogels with layered hierarchical pores were prepared by freeze-drying. The ultrafine fibers obtained in step (2) were dispersed in deionized water to prepare a 1.5 wt% suspension, which was ultrasonically dispersed for 90 min. The suspension was poured into a square freeze mold and pre-frozen at -60℃ for 24 h to allow ice crystals to grow in an oriented manner. The gel was then transferred to a freeze dryer and dried at a vacuum of 5 Pa and a temperature of -50℃ for 72 h to obtain nanofiber-derived aerogels with an oriented layered pore structure.
[0035] (4) Radiation-resistant nanoporous aerogels were in situ composited in nanofiber-derived aerogels using a sol-gel combined supercritical drying method; tetraethyl orthosilicate (TEOS), ethanol, and deionized water were mixed in a molar ratio of 1:9:7, and ammonia was used as a catalyst (accounting for 1.2% of the total mass of the sol) to prepare a silica sol. Europium nitrate (Eu) was added... 3+ (Source) dissolves in ethanol, controlling Eu 3+ The molar concentration was 0.10 mol / L, and the doped solution was mixed with silica sol at a volume ratio of 1:8. The nanofiber-derived aerogel obtained in step (3) was immersed in the above sol and impregnated for 50 min under a vacuum of 0.07 MPa to ensure that the sol fully penetrated into the pores inside the fiber. The impregnated sample was placed in a sealed container and allowed to stand at 55℃ for 20 h to allow the sol to gel in situ, and then aged at 55℃ for 48 h. The solvent was replaced with anhydrous ethanol every 10 h for 5 days. Finally, supercritical drying was carried out with ethanol as the medium at a temperature of 270℃ and a pressure of 11 MPa for 5 h to obtain ultrafine carbon fiber pre-oxidized cotton reinforced Eu with temperature sensing function. 3+ SiO2-doped aerogel composite material.
[0036] The ultrafine fiber reinforced aerogel composite material prepared in this embodiment has a room temperature thermal conductivity of 0.030 W / (m·K), an average sound insulation of 30 dB in the 500~2000 Hz range, and a specific surface area retention rate of 91.8% after 1700 kGy γ irradiation, with a thermal conductivity increase of <9%. Simultaneously, the embedded Ti... 3+ Doping with VO2 powder imparts reversible thermochromic properties (deep blue → orange-red) at 510–580°C, with a temperature shift of <8°C after 100 thermal cycles. A carbon fiber-silica aerogel composite material disclosed in patent CN116063061A has a thermal conductivity of 0.02–0.40 W / (m·K), a compressive strength of 0.1–0.3 MPa, and a 5 wt% thermogravimetric temperature of 500–800°C. While this comparative material can achieve thermal conductivity close to that of this embodiment under certain formulations, it does not incorporate any radiation resistance design, and carbon fiber has poor heat resistance in air (difficult to exceed 500°C). This embodiment, however, uses pre-oxidized carbon fiber cotton combined with rare-earth Eu. 3+ Doping not only ensures irradiation stability but also endows materials with temperature sensing capabilities, giving them significant advantages in terms of service reliability and functional versatility in the high-temperature radiation environment of nuclear power plants.
[0037] Example 4 A temperature-sensing ultrafine quartz fiber reinforced Sm240 microstructure for use in the insulation of sodium-cooled fast reactor steam generators 3+ / Dy 3+ Co-doped SiO2 aerogel composite material. Contains Ga with temperature sensing capabilities. 3+ VO2-doped inorganic units are uniformly coated onto an ultrafine quartz fiber framework in the form of a coating, and combined with radiation-resistant Sm 3+ / Dy 3+ A co-doped SiO2 nanoporous aerogel composite. When used in nuclear power plants, this composite material is coated onto the outer layer of insulation material, and its temperature and insulation effect are indicated in real time through reversible color changes. The volume fraction of inorganic units is 22%, the volume fraction of the fiber skeleton is 25%, and Ga... 3+ The doping concentration was 1.5 mol%, and the coating thickness was 30 μm.
[0038] The method for preparing ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power, in which inorganic units are uniformly coated onto an ultrafine fiber skeleton in the form of a coating, includes the following steps: (1) Ultrafine quartz fibers were prepared by centrifugal blowing method; (2) Temperature-sensing inorganic units were composited on the surface of ultrafine fibers using a hydrothermal synthesis method to prepare ultrafine fibers with temperature sensing function. Vanadium pentoxide (V2O5), hydrazine hydrate (N2H4·H2O, concentration 80%) and gallium nitrate (doped metal source) were added in a molar ratio of 1:1.8:0.015. A certain amount of V2O5 was dispersed in deionized water to make the total V concentration in the solution reach 0.3 mol / L. Hydrazine hydrate was slowly added and gradually dissolved under stirring. The solution changed from yellow to dark blue. Gallium nitrate was added according to the above molar ratio and stirring was continued until completely dissolved. The pH was adjusted to 2.5~3.0 with nitric acid to prevent precipitation and facilitate the subsequent formation of VO2 phase. The mixed solution and the ultrafine quartz fibers obtained in step (1) were placed together in a hydrothermal reactor at a mass ratio of 25:1 and kept at 200℃ for 16 h. After cooling, the solution was washed with deionized water until neutral and dried at 90℃ for 10 h. Finally, calcination was carried out at 450℃ for 2 h under a nitrogen atmosphere to obtain Ga-coated surface. 3+ Ultrafine quartz fibers doped with VO2 coating, with a coating thickness of approximately 30 μm.
[0039] (3) The ultra-thin felt was prepared by using a water-based self-assembly method to prepare ultra-fine fibers with temperature sensing function. The functionalized fibers obtained in step (2) were dispersed in deionized water, ultrasonically treated for 40 min, 2.0 wt% acrylate binder was added, and mechanically stirred to mix. The solid content of the slurry was controlled to be 12 wt%, and stirred at 1500 rpm for 80 min. The slurry was pumped into a vacuum filtration molding system, and the vacuum degree was controlled to be 0.06 MPa, so that the fibers were deposited on the mesh belt to form a wet felt. The felt was dried at 100℃ for 8 h to obtain an ultra-thin felt with a thickness of 1.5 mm.
[0040] (4) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in-situ composited in an ultrathin felt to obtain a microfiber-reinforced aerogel composite material with temperature sensing function for nuclear power applications; TEOS, ethanol, and deionized water were mixed in a molar ratio of 1:10:8, and a silica sol was prepared using hydrochloric acid as a catalyst (0.8% of the total sol mass). Samarium nitrate (Sm... 3+ ) and dysprosium nitrate (Dy 3+ Dissolve in deionized water to control Sm 3+ and Dy 3+The molar concentration of each component was 0.06 mol / L (total doping concentration 0.12 mol / L), and the doping solution was mixed uniformly with silica sol at a volume ratio of 1:15. The ultrathin felt obtained in step (3) was immersed in the sol and impregnated for 70 min under a vacuum of 0.09 MPa. The impregnated sample was placed in a sealed container and allowed to stand at 65℃ for 28 h to gel, and then aged at 65℃ for 56 h. The solvent was replaced with anhydrous ethanol every 12 h for 6 days. Supercritical CO2 drying was used at a temperature of 300℃, a pressure of 14 MPa, and a drying time of 6 h to finally obtain ultrafine silica fiber reinforced Sm with temperature sensing function. 3+ / Dy 3+ Co-doped SiO2 aerogel composite material.
[0041] The ultrafine fiber reinforced aerogel composite material prepared in this embodiment has a room temperature thermal conductivity of 0.026 W / (m·K), an average sound insulation of 27 dB in the 500~2000 Hz range, and a specific surface area retention rate of 93.5% after 1700 kGy γ irradiation, with a thermal conductivity increase of <7%. Meanwhile, Ga... 3+ The VO2-doped coating exhibits reversible thermochromic changes (yellow-green → dark brown) at 375–440°C, with a response time ≤1.5 s and an accuracy of ±2°C. The contrast retention rate after irradiation is >90%. Patent CN115449219A discloses a method for preparing a silica aerogel / quartz fiber / polyimide ternary composite material with a thermal conductivity of 0.5–0.6 W / (m·K) and a density ≤1.70 g / cm³. 3 The compressive strength is 570~650 MPa. While the comparative material has extremely high mechanical strength, its thermal conductivity is 19~23 times that of this embodiment, and the upper temperature limit of the polyimide matrix is only about 500°C, which cannot meet the long-term service requirements of nuclear power plants at high temperatures (300~600°C), and it also lacks radiation resistance and temperature sensing capabilities. This embodiment, while maintaining extremely low thermal conductivity, utilizes Sm... 3+ / Dy 3+ Co-doping achieves excellent radiation resistance and reversible color change temperature indication function, giving it an irreplaceable technological advantage in the field of nuclear power insulation materials.
[0042] The above description is merely a preferred embodiment of the present invention. However, the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention should be covered within the scope of protection of the present invention.
Claims
1. An aerogel composite material with temperature sensing function, characterized in that, It is composed of an inorganic unit modified ultrafine fiber skeleton with temperature sensing function to enhance radiation-resistant nanoporous aerogel. The inorganic unit is uniformly coated on the ultrafine fiber skeleton in the form of a coating, uniformly dispersed between the ultrafine fiber skeleton in the form of powder, and / or uniformly dispersed inside the ultrafine fiber skeleton in the form of powder. The volume fraction of the inorganic unit is 15% to 25%, and the volume fraction of the ultrafine fiber skeleton is 20% to 35%. The inorganic unit is Al 3+ Doping with VO2, Ga 3+ Doping with VO2 and Cr 3+ Doping with VO2 and Ti 3+ Doping with VO2 or Cr 3+ Doping with Al2O3, in which Al 3+ Doping concentration of 1.0~5.0 mol% Ga 3+ The doping concentration is 0.5~3.0 mol%, Cr 3+ The doping concentration is 0.8~4.0 mol%, Ti 3+ Doping concentration is 0.5~6.0 mol%, Cr 3+ Cr in Al2O3 3+ The doping concentration is 1~8.0 mol% The ultrafine fibers in the ultrafine fiber skeleton are one or more of the following: glass fiber, carbon fiber pre-oxidized cotton, mullite fiber, quartz fiber, alumina fiber, zirconium oxide fiber, and silicon carbide fiber. The radiation-resistant nanoporous aerogel is Gd 3+ Eu 3+ 、Sm 3+ Er 3+ Dy 3+ B 3+ One or more ion-doped SiO2 aerogels.
2. The application of the aerogel composite material with temperature sensing function as described in claim 1 in a nuclear power plant, characterized in that, When used in nuclear power plants, a temperature-sensing aerogel composite material is wrapped around the outer layer of the insulation material. The color change of the temperature-sensing aerogel composite material is used to detect its true temperature and true insulation effect in the service environment, indicating and warning of damage. The temperature sensing range of the temperature-sensing aerogel composite material is 300~600°C.
3. A method for preparing an aerogel composite material with temperature sensing function according to any one of claims 1, characterized in that, When inorganic units are uniformly coated onto a microfiber skeleton in the form of a coating, the following steps are included: (3.1) Ultrafine fibers are prepared by flame blowing or centrifugal blowing; (3.2) Ultrafine fibers with temperature sensing function are prepared by compositing inorganic units with temperature sensing function on the surface of ultrafine fibers using a hydrothermal synthesis method. The coating thickness of the inorganic unit is 0.1~500 μm. (3.3) Use a water-based self-assembly method to prepare ultra-thin felt from ultrafine fibers with temperature sensing function; (3.4) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in an ultrathin felt to obtain an ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power. When inorganic units are uniformly dispersed in powder form between ultrafine fiber skeletons, the following steps are included: (4.1) Ultrafine fibers are prepared by flame blowing or centrifugal blowing methods; (4.2) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; (4.3) Microspheres of inorganic unit powder coated with SiO2 with temperature sensing function were prepared by the interface confined sol-gel method. The microspheres have a core-shell structure with a shell thickness of 20~1000 nm. (4.4) Using ultrafine fibers and SiO2 coated inorganic unit microspheres with temperature sensing function as raw materials, an ultrathin felt loaded with inorganic unit powder with temperature sensing function was prepared by water-based self-assembly method; (4.5) Using a sol-gel combined supercritical drying method, radiation-resistant nanoporous aerogels were in situ composited in an ultrathin felt to obtain an ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power. When inorganic units are uniformly dispersed in powder form within an ultrafine fiber skeleton, the following steps are included: (5.1) Inorganic unit powder with temperature sensing function was prepared by precursor impregnation-thermal diffusion method; (5.2) Ultrafine fibers with embedded inorganic unit powders having temperature sensing function are prepared by electrospinning or centrifugal spinning. (5.3) Nanofiber-derived aerogels with layered multi-level pores were prepared by water-based self-assembly or freeze-drying methods; (5.4) Radiation-resistant nanoporous aerogels were in situ composited in nanofiber-derived aerogels using a sol-gel combined supercritical drying method.
4. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In step (3.2), the hydrothermal synthesis method includes the following steps: When the inorganic unit is doped with VO2: ① A solution is prepared by dissolving a vanadium source, a reducing agent, and a doped metal salt in deionized water. The vanadium source is ammonium metavanadate or vanadium pentoxide, the reducing agent is oxalic acid or hydrazine hydrate, and the doped metal salt is aluminum nitrate, gallium nitrate, chromium nitrate, or tetrabutyl titanate. ② Adjust the pH to the appropriate range using hydrochloric acid or nitric acid; ③ Place the mixed solution and ultrafine fibers together in a reaction vessel and keep it at a constant temperature for reaction; ④ After cooling, wash with deionized water until neutral, and then dry. ⑤ Calcination under an inert atmosphere yields ultrafine fibers with surface-coated modified VO2. When the inorganic unit is Cr 3+ When doped with Al2O3: ① A solution is prepared by dissolving an aluminum source and a chromium source in deionized water, wherein the aluminum source is aluminum isopropoxide or aluminum nitrate, and the chromium source is chromium nitrate; ② Add α-Al2O3 or magnesium oxide as a phase transition inhibitor; ③Immerse the microfiber in the above solution and perform vacuum impregnation; ④ After drying, calcination is carried out in air to obtain a Cr-coated surface. 3+ Ultrafine fibers doped with modified Al2O3.
5. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In steps (3.3), (4.4), and (5.3), the water-based self-assembly method includes the following steps: ①Using deionized water as a solvent, ultrafine fibers with temperature sensing function are added to the solvent and ultrasonically treated to make the fibers uniformly dispersed, thus preparing an ultrafine fiber dispersion. ② Add acrylate or polyvinyl alcohol as a binder to the above dispersion, and mechanically stir to mix it evenly to obtain ultrafine fiber slurry; ③ When preparing the ultrathin felt in step (3.3), control the slurry to the appropriate solid content, stir it evenly, and then draw the slurry into the molding system. Use vacuum filtration to assist molding, so that the fibers are deposited on the molding mesh to form a wet felt, and then dry it to obtain the ultrathin felt. ④ When preparing the ultrathin felt in step (4.4), SiO2-coated inorganic unit microspheres are added to the ultrafine fiber dispersion and ultrasonically dispersed to make them uniformly mixed; the slurry is controlled to an appropriate solid content, stirred evenly, and then the slurry is drawn into the molding system. Vacuum filtration is used to assist molding, so that the fibers and microspheres are deposited on the molding mesh belt to form a wet felt, which is then dried to obtain an ultrathin felt loaded with inorganic unit powder with temperature sensing function; ⑤ When preparing nanofiber-derived aerogel in step (5.3), the slurry is divided into two types: type A (high concentration) and type B (low concentration). Layered vacuum filtration is used to assist in molding. First, type A slurry is filtered to form the bottom layer, and then type B slurry is filtered to form the top layer. The total thickness is controlled, and after gradient drying, nanofiber-derived aerogel with a layered multi-level pore structure is obtained.
6. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In steps (3.4), (4.5), and (5.4), the sol-gel combined supercritical drying method includes the following steps: ① Prepare a silica sol by mixing tetraethyl orthosilicate, ethanol, and deionized water, using hydrochloric acid or ammonia as a catalyst; dissolve the doped metal source in deionized water or ethanol, the doped metal source being gadolinium nitrate, europium nitrate, samarium nitrate, erbium nitrate, dysprosium nitrate, or boric acid, and mix the doped solution with the silica sol evenly. ②Immerse the ultrathin felt from steps (3.3) and (4.4) or the nanofiber-derived aerogel from step (5.3) into the sol prepared in ①, and vacuum impregnate to allow the sol to fully penetrate into the fiber network and achieve in-situ composite; ③ Place the impregnated sample in a sealed container and let it stand to allow the sol to gel in situ within the fiber skeleton; ④ Continue aging the gel composite system to enhance the strength of the gel network; ⑤ Use anhydrous ethanol to replace the solvent and remove unreacted substances and water; ⑥Using ethanol or carbon dioxide as the drying medium, supercritical drying is carried out to finally obtain ultrafine fiber reinforced aerogel composite material with temperature sensing function for nuclear power.
7. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In steps (4.2) and (5.1), the precursor impregnation-thermal diffusion method includes the following steps: A vanadium or aluminum source is dispersed in deionized water to form a suspension. Polyvinyl alcohol is added and the mixture is ultrasonically treated. A doped metal source, such as aluminum nitrate, gallium nitrate, chromium nitrate, or tetrabutyl titanate, is then added. The mixture is heated and stirred in a water bath. The solution is aged at room temperature and then dried to obtain a precursor block. The precursor block is placed in a muffle furnace or tube furnace and heated at a set rate before calcination in an air, nitrogen, or argon atmosphere. The calcined product is cooled to room temperature, ground, and sieved to obtain an inorganic unit powder with temperature sensing function.
8. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In step (4.3), the interface-confined sol-gel method includes the following steps: ① The inorganic unit powder was dispersed in an ethanol / oxalic acid mixed solution, and hexadecyltrimethylammonium bromide was added for surface activation; ② Add tetraethyl orthosilicate solution dropwise and adjust the pH to the appropriate range; ③ The mixed solution was stirred and reacted under water bath conditions. After interfacial confinement condensation, the mixed solution was allowed to stand and age at room temperature. The aged suspension was centrifuged and the precipitate was collected. The precipitate was washed alternately with deionized water and anhydrous ethanol. After each washing, the precipitate was centrifuged and dried to obtain microspheres of inorganic unit powder with SiO2 coating and temperature sensing function.
9. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In step (5.2), the electrospinning method includes the following steps: ① A spinning solution is prepared by dissolving polyvinylpyrrolidone or polyvinylidene fluoride as the spinning polymer in N,N-dimethylformamide or ethanol; ② Add inorganic unit powder with temperature sensing function; ③ After ultrasonic dispersion, a crosslinking agent is added, which is glutaraldehyde or N,N-methylenebisacrylamide, and mechanical stirring is performed to obtain a uniform spinning solution; ④ Inject the spinning solution into the electrospinning equipment and set the corresponding process parameters to obtain the precursor fiber; ⑤ The precursor fiber is calcined to remove organic components. The calcination atmosphere is air to obtain ultrafine fibers with embedded inorganic units. In step (5.2), the centrifugal spinning method includes the following steps: ① A polymer solution is prepared by dissolving polyacrylonitrile or polylactic acid as the spinning polymer in dimethyl sulfoxide or acetone; ② The inorganic unit powder is mixed with the polymer solution and ultrasonically dispersed to obtain a stable spinning solution; ③ Add the spinning solution to the centrifugal spinning equipment and set the corresponding process parameters to collect the fibers; ④ After collection, the fibers are pre-oxidized in an air atmosphere; ⑤ Carbonization under nitrogen or argon protection yields ultrafine fibers with embedded inorganic units that have temperature sensing function.
10. The method for preparing an aerogel composite material with temperature sensing function according to claim 3, characterized in that, In step (5.3), the freeze-drying method includes the following steps: ① The ultrafine fibers with embedded temperature-sensing inorganic unit powder are dispersed in deionized water to form a suspension, which is then ultrasonically dispersed evenly. ② Pour the fiber suspension into a freezing mold and pre-freeze to form a gel; ③ Transfer the gel to a freeze dryer and freeze dry to obtain a nanofiber-derived aerogel with layered multi-level pores.
Citation Information
Patent Citations
Silicon dioxide aerogel, quartz fiber and polyimide ternary composite material as well as preparation method and application thereof
CN115449219A
Preparation method of nano silicon dioxide fiber reinforced aluminum oxide aerogel composite material
CN116023165A
Carbon fiber-silicon dioxide aerogel composite material as well as preparation method and application thereof
CN116063061A
Glass fiber reinforced silicon dioxide aerogel as well as preparation method and application thereof
CN121517186A
